PENERAPAN METODE THINK TALK WRITE (TTW) DALAM MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN GEOGRAFI KELAS VIII-G SEMESTER GANJIL SMP NEGERI 1 PANJI - Arico Ayani Suparto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The objectives of this study are 1) To determine the application of the Think Talk Write (TTW) method in improving student learning outcomes in Geography class VIII-G class in the odd semester of SMP Negeri 1 Panji. 2) To determine the increase in student learning outcomes in the process of implementing the Think Talk Write (TTW) method in Geography in class VIII-G in the odd semester of SMP Negeri 1 Panji. 3) For experience / learning for researchers in practicing the knowledge gained while in college and for continuing similar research. The research subjects were students of class VIII G SMP Negeri 1 Panji, with the number of research objects being 36 students. This research uses a qualitative approach and the type of research is classroom action research. Data collection methods used were interviews, observation and tests. Data collected in the form of teacher activities, interview results and test results. The research was conducted in two cycles, and each cycle consisted of two meetings. The Think Talk Write (TTW) learning model is very interesting because in the delivery of material students are invited to think and be active, so that students can easily understand the material being studied. In Think Talk Write (TTW) learning, students seem active, especially in group discussion activities. The results obtained from this study were the percentage of classical learning completeness in the pre-action treatment was 44.44%, while the first cycle was 77.8% and the second cycle experienced an increase in the number of obtaining 100%. Based on the results of data analysis, it can be concluded that the application of the Think Talk Write learning method can be used as a technique to improve student activity and learning outcomes.